The world since 1945 an international history - Bell, P. M. H. (Philip Michael Hett) 1930-; Gilbert, Mark 1961- (Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2017)
"A comprehensive survey of international affairs from the end of the Second World War, through to the Cold War and up to the present day"--Provided by publisher.